Attitude of the women farmers towards organic farming of Nilphamari district in Bangladesh - Sarwar, Md Golam; Mondol, Md Abu Sayed; Goswami, Pallab; Huda, Saiful (International Journal of Agricultural Research, Innovation and Technology, 2022)
The key objective of the study was to determine the extent of attitude of the women farmers towards organic farming. The study was conducted in two union of Nilphamari Sadar upazila such as Lakshmi Chap and Palashbari under Nilphamari district. Total 100 women farmers were selected from the study area as the population and random sample techniques was used to comprised of 80 constituted the sample of the study. Data were collected by a pre-tested interview schedule during 25 April to 25 May 2020. Simple and direct questions with different scales were used to obtain information. Attitude of the women farmers towards organic farming was measured by Likert scale. Descriptive statistics, multiple regression was used for analysis. Slightly above three-fifths (63.7 percent) of the women farmers had moderately favorable attitude towards organic farming while 21.3 percent slightly favorable attitude and 15.0 percent of women farmers under highly favorable attitude towards organic farming. It is noticed that the majority (85.0 percent) of the women farmers showed slightly favorable to moderately favorable attitude towards organic farming. Educational qualification, training experience, and access to extension contact of the respondents had significant positive contribution with their attitude towards organic farming. The most important problem (77.50 percent) faced by the women farmers was “higher amount of insect pest and diseases”. The foremost (67.50 percent) suggestion offered by the women farmers was “Developing organic pesticide company through private and government initiatives”. Int. J. Agril. Res. Innov. Tech. 12(1): 174-181, June 2022